ISLAMIC APOCALYPTIC LITERATURE AND EXTREMISM: CONTEXTUAL READING OF HADITHS ON THE MAHDI WITH SPECIAL REFERENCE TO SRI LANKA - Mohammad Ismath Ramzy; Rahimi Md Saad; Rohan Gunaratna (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
Like any other religious community, the apocalyptic literature in Muslim society has become a source of pessimism instead of optimism. The extremists who conducted a series of suicide attacks on religious places and hotels in Sri Lanka in 2019 justified their violent activities, referring to apocalyptic literature that prophesied the advance of Mahdi. These extremists misunderstood the hadiths on the Mahdi and intended to create instability in the world to accelerate his coming to resolve the present issues of Muslims. This research studied the relevant hadiths quoted by the extremists to kill innocent people and explored their meaning. The contextual analysis method has been employed to extract the meaning of these hadiths. This research shows that the extremists have misinterpreted these hadiths and used the Islamic apocalyptic literature out of context. The socio-political context of the usage of these hadiths further elaborates the change that has taken place in the understanding of their purpose throughout history. Therefore, this research recommends that Muslim religious and social leaders review interpretation traditions and educate young people to adopt socio-political and historical contexts to understand Islamic apocalyptic literature, mainly hadiths, to protect young people from extremism and radicalism.